Impact of control release fertilizers on vegetative, gas exchange attributes and nutrient status of Philodendron erubescens - Shanthanu R; Keisar Lourdusamy D; Kavino M; Chitra R; Prabu P C; Vanitha K (Plant Science Today, 2024)
Philodendron erubescens, commonly known as the Red-leaf Philodendron or Blushing Philodendron, is a popular ornamental plant species belonging to the family Araceae. Due to the bright red colour, this species is one of the leading indoor plants in commercial market. The current study investigated the efficacy of controlled-release fertilizers (CRFs) in accelerating the growth of tissue-cultured Philodendron erubescens (Pink Princess) to commercial saleable size in a nursery setting. Two CRF treatments - Basacote high K 6 M + hydrospeed CaB-Max and organic CRF + hydrospeed CaB-Max were compared against control using conventional water-soluble fertilizer. Forty-five-day-old tissue-cultured plantlets were evaluated over 60 days for morphological parameters, root development, physiological responses and nutrient uptake. A CI-340 Handheld photosynthesis machine was employed to measure photosynthetic rate, transpiration rate and stomatal conductance. Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) was used for precise quantification of foliar macro- and micronutrient concentrations. Results demonstrated that Basacote high K 6 M + hydrospeed CaB-Max significantly outperformed both organic CRF + hydrospeed CaB-Max and the control in accelerating plant growth to commercial standards. Basacote high K 6 M + hydrospeed CaB-Max treated plants reached a mean height of 28.48 cm and spread of 27.09 cm after 60 days, approaching the target saleable size of 25 to 30 cm. Root morphology analysis using WinRHIZO software revealed enhanced root system development in Basacote high K 6 M + hydrospeed CaB-Max plants, indicating improved establishment. Physiological measurements showed higher photosynthetic rates (11.46 ?mol m?² s?¹), transpiration rates (1.32 mmol m?² s?¹) and stomatal conductance (30.97 mmol m?² s?¹) in Basacote high K 6 M + hydrospeed CaB-Max plants. ICP-MS analysis indicated superior nutrient uptake and accumulation in T1-treated plants, particularly for calcium, potassium, magnesium and iron. Strong positive correlations between physiological parameters and morphological traits suggest that enhanced nutrient availability from CRFs contributed to accelerated growth and improved plant quality. This study elucidates the potential of tailored CRF formulations to optimize the rapid establishment of tissue-cultured P. erubescens into marketable plants, offering valuable insights for commercial nursery production practices.